A technical approach to equity investing in emerging markets. Issue 3 (13th October 2018) - Metghalchi, Massoud; Hayes, Linda A.; Niroomand, Farhang
Abstract: Technical analysis (TA) is used in evaluating its predictive power for the Morgan Stanley Capital International (MSCI) Emerging Market Index (EMI) that reflects 23 emerging market economies' equity indices. We conclude strong predictive power of technical analysis for the EMI. Given this predictive power of TA, we then investigate whether investors can exploit this predictive power to beat the profitability of the Buy‐and‐Hold strategy considering both risk and transaction costs. Applying Moving Average, Relative Strength Index, Moving Average Convergence Divergence, and Rate of Change trading rules to the MSCI Emerging Market Index over the period of 11/1/1988 to 5/1/2017 reveals strong empirical evidence that investors could use TA to out‐perform the Buy‐and‐Hold strategy even when considering risk and transaction costs. This research provides evidence against the Efficient Market Hypothesis for EMI.